2021
DOI: 10.3390/nano11020407
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Silent Aspect of Carbon Nanopores

Abstract: Recently, owing to the discovery of graphene, porous carbons experienced a revitalization in their explorations. However, nowadays, the focus is more on search for suitable energy advancing catalysts sensing, energy storage or thermal/light absorbing features than on separations. In many of these processes, adsorption, although not emphasized sufficiently, can be a significant step. It can just provide a surface accumulation of molecules used in other application-driving chemical or physical phenomena or can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…The surface-bound organic matter (e.g., protein) in the eggshell could be liberated during the calcination step to yield a higher surface area than the CaCO3 counterpart [26,39]. In line with the above discussion, it has been previously reported that such pores and defects often determine the overall catalytic activity [22,72]. The best-performing catalyst (Ag-1.5%-MnO2/Eggshell-R) was utilized for further experiments to evaluate the effect of process variables on FA oxidation.…”
Section: Evaluation Of the Fa Catalytic Oxidation Performancementioning
confidence: 54%
“…The surface-bound organic matter (e.g., protein) in the eggshell could be liberated during the calcination step to yield a higher surface area than the CaCO3 counterpart [26,39]. In line with the above discussion, it has been previously reported that such pores and defects often determine the overall catalytic activity [22,72]. The best-performing catalyst (Ag-1.5%-MnO2/Eggshell-R) was utilized for further experiments to evaluate the effect of process variables on FA oxidation.…”
Section: Evaluation Of the Fa Catalytic Oxidation Performancementioning
confidence: 54%
“…If the structure shown in figure 7 is correct it has consequences for understanding the properties of microporous carbons. Whether they are employed as adsorbents or in other applications such as lithium-ion batteries and supercapacitors, the properties of the carbons depend critically on the size and shape of the pores [38,39]. A very common assumption in modelling studies of microporous carbons is that the pores are slit-shaped, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the regards of environmental remediation applications, other kind of carbonaceous materials, especially based on porous carbon or/and biochar, was shown to have ultimately high adsorptive capability against not only organic pollutants, but also against (heavy) metals [ 161 , 162 ]. The recent trend on materials design is to utilize undesired biomass and wastes as feedstock and after thermal treatment (carbonization) or/and activation to obtain bulky carbons/biochars [ 20 , 163 , 164 , 165 ] with the ultimate goal of the final material to possess high surface chemistry heterogeneity, high porosity and ultimately a micro-/nano-porous nature [ 12 , 13 ]. However, this aspect is outside the scope of this work, since the literature is very abundant in this kind of high value reviews and research articles.…”
Section: Photo- and Sono-catalytic Selective Oxidation Of Hmf And Dec...mentioning
confidence: 99%
“…Activated porous carbons or biochar (APCs), although not considered as nanomaterials, have attracted research interest and have reached wide commercialization in the fields of adsorbent and catalyst manufacturing. The properties of APCs that make them ideal for such applications are their tunable surface chemistry, the high surface area and pore volume induced by the nanosized micro/mesopores, and their exceptional chemical and dimensional stability in aqueous or various organic media [ 11 , 12 , 13 , 14 ]. In general, the APCs can be obtained via various synthetic approaches/routes.…”
Section: Introductionmentioning
confidence: 99%